Practices of the students of the Baguio City High School in the purchase of health goods and services their implications to health education - Bautista, Priscilla (Andaya) 1935- (s.n.], 1973)
This study investigated the practice of students in the Baguio City High School that may affect their health and their implications to health education. The findings of this study may be utilized by health teachers, supervisors, and administrators as guidelines in proposing programs in health education in high school particularly in the area of consumer education.